Autumn - Smith, Ali, 1962- (Pantheon Books, 2016)
"From the Man Booker-shortlisted and Baileys Prize-winning author of How to be both: a breathtakingly inventive new novel--about aging, time, love, and stories themselves--that launches an extraordinary quartet of books called Seasonal. Readers love Ali Smith's novels for their peerless innovation and their joyful celebration of language and life. Her newest, Autumn, has all of these qualities in spades, and--good news for fans!--is the first installment in a quartet. Seasonal, comprised of four stand-alone books, separate yet interconnected and cyclical (as are the seasons), explores what time is, how we experience it, and the recurring markers in the shapes our lives take and in our ways with narrative. Fusing Keatsian mists and mellow fruitfulness with the vitality, the immediacy, and the color hit of Pop Art, Autumn is a witty excavation of the present by the past. The novel is a stripped-branches take on popular culture and a meditation, in a world growing ever more bordered and exclusive, on what richness and worth are, what harvest means"--